2015
DOI: 10.1007/s00726-015-2070-6
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin β4 induces proliferation, invasion, and epithelial-to-mesenchymal transition of oral squamous cell carcinoma

Abstract: The epithelial-to-mesenchymal transition (EMT) plays a vital role in carcinogenesis, invasion, and metastasis of many epithelial tumors including oral squamous cell carcinoma (OSCC), a common malignancy of the head and neck. However, the functional role of the actin-sequestering protein thymosin β4 (Tβ4) in the EMT in OSCCs remains unclear. Thus, we investigated whether overexpression of Tβ4 could induce in vitro tumorigenesis such as cell proliferation and anchorage independency and an EMT-like phenotype in O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…It reduces the activation of depolymerization of ADF/cofilin. This subsequently interferes with actin depolymerization, promotes actin cytoskeletal remodeling and cell pseudopodia formation, and induces EMT, thereby promoting tumor invasion and metastasis3649. The present study further confirmed that the expression and phosphorylation levels of LIMK1 significantly increased during colon cancer cell invasion and migration.…”
Section: Discussionsupporting
confidence: 81%
“…It reduces the activation of depolymerization of ADF/cofilin. This subsequently interferes with actin depolymerization, promotes actin cytoskeletal remodeling and cell pseudopodia formation, and induces EMT, thereby promoting tumor invasion and metastasis3649. The present study further confirmed that the expression and phosphorylation levels of LIMK1 significantly increased during colon cancer cell invasion and migration.…”
Section: Discussionsupporting
confidence: 81%
“…It was shown for hepatoblastoma and oral squamous cell carcinoma that Tβ4 induced EMT transition (Fu et al, 2015;Hong et al, 2016). Here, we demonstrate that also in melanoma cells there is a connection between TMSB4X expression and EMT progression.…”
Section: Discussionsupporting
confidence: 66%
“…DADS downregulates LIM kinase-1 (LIMK1), vimentin and EMTrelated proteins (Slug, Snail), and upregulates E-cadherin and TIMP-3 (tissue inhibitor of metalloproteinase-3) expression which are the signs of the occurrence of EMT, suggesting that DADS may reverse EMT by downregulating LIMK1 [97,98]. DADS suppresses actin cytoskeletal remodeling and cell pseudopodia formation, and the occurrence of EMT via down regulating LIMK1 expression to decrease the expression of vimentin, CD34, and Ki-67; increase E-cadherin expression; and impede cancer cell proliferation, angiogenesis, and EMT alteration, thereby inhibiting invasion and metastasis [98][99][100]. Actually, the effects of DADS on E-cadherin and vimentin expression may result in blockage of the ERK/Fra-1 pathway by inhibition of LIMK1 expression and activity.…”
Section: Inhibition Of Tumor Metastasis By Dadsmentioning
confidence: 99%